The Influence of Mass Media Channels on Mental Illness Stigmatization among Students in Kenya Medical Training College - Maina J. Kamau; Kenneth Goga Riany (Budapest International Research and Critics University, 2023)
Mental illnesses have been known to distress the general population as a whole. Notably, no social demographic is exempt from mental illnesses with the modern dynamics and challenges increasing the magnitude of mental illness. Students especially in higher learning institutions are not spared from the over-increasing mental illnesses. Despite the challenges brought about by mental illnesses among the students, stigmatization of the mentally ill has been high among them. This has seen increased drop-out of school, total insanity and sometimes suicide due to lack of psychosocial support among the mentally ill students, especially their peers. The mass media has been a critical tool of communication. However, there is little evidence on its role in mental health stigmatization hence this study seeks to assess the role of mass media channels on the mental illness stigmatization among college students. The research utilized the descriptive survey design and where both qualitative and quantitative methods were used to collect and analyze the data. The target population of this study comprised of the students at the Kenya Medical Training College (KMTC). There were 51045 students in the college as of July 2022. A questionnaire was used to collect data from the students. The data was analysed using mixed method analysis where both quantitative and qualitative data was analysed. The quantitative data was analysed using inferential and descriptive statistics through SPSS. Content analysis was used to analyse the qualitative data. The findings revealed that mass media channels played a critical role in determining the spread of information and the perceptions of mental illness among students. The channels of mass media communication were found to instigate mental illness stigmatization among college students. Digital media was found to have the strongest influence on mental health stigmatization followed by broadcasting media, print media and outdoor media. It is recommended that these channels of mass media ought to be more positive and encourage students to uphold and accept the mentally ill to minimize stigmatization.